Causal effects of atopic dermatitis and rosacea on ventricular structure and function - Wei Wu; Guo-Liang Huang; Jia Cui (Medicine, 2026)
Rosacea and atopic dermatitis (AD) are 2 chronic inflammatory skin diseases. Studies have revealed that patients with rosacea and AD exhibit elevated risks of cardiovascular disease. However, the impact of these conditions on the ventricular structure and function remains to be elucidated. This study employed a two-sample Mendelian randomization (MR) approach, utilizing genetic variants as instrumental variables, to explore the genetic associations between rosacea and AD with alterations in ventricular function (including stroke volume and ejection fraction) and structural ventricular variations (including end-diastolic volume and end-systolic volume). The research design adhered to 3 core assumptions. Primary analyses were performed using the inverse-variance weighted method, complemented by 4 additional MR models and sensitivity analyses to ensure robustness. Additionally, multivariate MR was further integrated to adjust for potential confounders, such as systolic blood pressure and diastolic blood pressure. Genetically predicted AD exhibited a positive association with right ventricular end-systolic volume (odds ratio = 1.3640, 95% confidence interval = 1.0002–1.8601, P = .0498). However, this association was no longer statistically significant after adjusting for systolic blood pressure and diastolic blood pressure. Furthermore, no causal association was observed between rosacea and ventricular parameters ( P > .05). Multiple sensitivity analyses confirmed the stability of the findings, with no evidence of horizontal pleiotropy ( P > .05). Genetic prediction suggested a potential link between AD and impaired right ventricular function. However, no significant causal associations were identified between rosacea and ventricular structural or functional parameters.